The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.31234/osf.io/4hbz3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The emergence of organized emotion dynamics in childhood

Abstract: Emotions change from one moment to the next. They have a duration from seconds to hours, and then transition to other emotions. Here we describe the early ontology of these key aspects of emotion dynamics. In five cross-sectional studies that combine parent surveys and ecological momentary assessment, we characterize how emotion duration and transitions change over the first five years of life, and how they relate to children’s language development. Over this developmental period, the duration of children’s em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…We tested this with a mixed-effects regression predicting the likelihood of the transition from the type of transition (same vs. cross valence), with random intercepts and slopes by participant and random intercepts by the second emotion in the transition. Replicating prior research (Nencheva et al, 2023;Thornton & Tamir, 2017), caregivers reported that they (𝛽 = 0.54, t(70.03) = 14.69, p = 4.53×10 -23 ) and their infants (𝛽 = 0.42, t(70) = 10.48, p = 5.44×10 -16 ) were more likely to transition between emotions with similar valence (e.g., between sad and angry) than between emotions with different valence (e.g., between sad and happy). This was very consistent across participants, with 66 (out of 70) of the adults reporting higher transition likelihoods for within vs. across valence transitions for themselves and 64 (out of 70) doing so for their child.…”
Section: Supplementary Materialsmentioning
confidence: 86%
See 3 more Smart Citations
“…We tested this with a mixed-effects regression predicting the likelihood of the transition from the type of transition (same vs. cross valence), with random intercepts and slopes by participant and random intercepts by the second emotion in the transition. Replicating prior research (Nencheva et al, 2023;Thornton & Tamir, 2017), caregivers reported that they (𝛽 = 0.54, t(70.03) = 14.69, p = 4.53×10 -23 ) and their infants (𝛽 = 0.42, t(70) = 10.48, p = 5.44×10 -16 ) were more likely to transition between emotions with similar valence (e.g., between sad and angry) than between emotions with different valence (e.g., between sad and happy). This was very consistent across participants, with 66 (out of 70) of the adults reporting higher transition likelihoods for within vs. across valence transitions for themselves and 64 (out of 70) doing so for their child.…”
Section: Supplementary Materialsmentioning
confidence: 86%
“…However, it is unknown how their fine-tuned knowledge of real-world emotion transition probabilities develops. Although young infants' transitions start out as more variable and idiosyncratic, they already follow this pattern of valence-driven transitions to an extent, as assessed by both caregiver reports and ecological-momentary assessment (Nencheva et al, 2023). Children converge to the adult-like pattern of valence-driven transitions by the age of five.…”
Section: Infants Track the Statistics Of Emotion Transitions In The Homementioning
confidence: 94%
See 2 more Smart Citations
“…Early childhood may be an especially important time for young children's development of valence‐based representations. Valence gradually emerges in the first 5 years of life as a dimension that organizes children's representations of nonlinguistic emotion cues and emotional experiences, in tandem with children's expanding vocabularies (Nencheva et al, 2021; Woodard et al, 2021). Children's ability to label emotions with specificity emerges during this same span in early childhood (Widen, 2013; Wu et al, 2022).…”
Section: Emotion Labels In Contextmentioning
confidence: 99%